Predictors of lexical availability in English as a second language - Ferreira, Roberto A.; Garrido Moscoso, Jaime I.; Guerra Rivera, Alexia (Onomázein, 2019)
Lexical availability measures the degree of availability of a word given a semantic context or category. It has been widely used in the Spanish-speaking world in order to derive words for use in dictionaries and/or teaching materials, but has received very little attention in English. The aim of this research was to identify the predictors of lexical availability (LA) in English as a second language (L2). Participants were 60 advanced students of English, enrolled in a 5-year English Teaching Programme. The lexical availability index (LAI) was obtained for two semantic categories (Body Parts, Food and Drink). Then correlation and multiple regression analyses were conducted in order to assess the relation between LA and four factors: familiarity, age of acquisition (AoA), frequency, and imageability. The results showed that both AoA and familiarity correlated highly with LA in Body Parts, but only AoA was a strong predictor of LA. In Food and Drink, familiarity and frequency had a moderate correlation with LA and only frequency was a significant predictor. These results are mostly in line with previous data in Spanish L1 and L2, and are of relevance for the learning and teaching of vocabulary in English L2.